The chemistry and magnetism of some rhenium and rhodium perovskite oxides - Hasanli, N (2019)
This work focuses on synthesis and characterisation of novel 4d and 5d materials with attention given to spin, orbital and lattice effects seen in metal oxides with heavy transition-metals.